Sprint speed characteristics of high-level American female soccer players: Female Athletes in Motion (FAiM) Study - Vescovi, J. D. (Journal of Science and Medicine in Sport, 2012)
Objectives: Sprint speed is important in soccer and while descriptions of male players are plentiful relatively few data exist for high-level female players. The aim of this study was to determine speed characteristics of high-level American female soccer players and evaluate if speed could distinguish between players selected (n = 56) and those not selected (n = 84) in a professional draft. Design: A cross-sectional study design. Methods: One hundred and forty women participating in a try-out for a professional soccer league had speed assessed over 35 m with splits at 5, 10 and 20 m. Speeds for the static start distances (5, 10, 20 and 35 m) as well as for `flying` splits (flying 5, 10, 25 and 30 m; also first 15 and final 15 m) were determined. Results: Mean speed over 5, 10, 20 and 35 m was 15.1±1.1, 18.0±0.9, 21.2±0.9 and 23.4±0.9 km h-1, respectively. Mean peak speed was 27.3±1.4 km h-1 and occurred during the final 15 m of the sprint (20-35 m). Speed for all flying splits exceeded 21.0 km h-1, with maximum values observed in excess of 30.0 km h-1. All speeds, except for the flying 5 m split, were faster in the drafted players compared to non-draftedplayers. Conclusions: These data indicate that elite female soccer players achieve speeds ranging between 22 and 26 km h-1 over distances of 15-20 mand can reach 27 km h-1 when evaluated over 35 m. Sprint speed was able to distinguish between drafted and non-drafted players.